ANALISIS TINDAK TUTUR EKSPRESIF DALAM KOLOM KOMENTAR PRODUK BACKPACK MOSSDOOM DI SHOPEE - Asma Gina; Burhan Sidik; Tanzilia Nur Fajriati (STKIP Subang, 2026)
The comment section on e-commerce platforms serves as a medium for buyers to express their experiences, evaluations, and feelings regarding the products they have purchased and used. These expressions indicate the use of expressive speech acts, which are worthy of investigation from a pragmatic perspective. This study aims to describe the types of expressive speech acts found in the comment section of the Mossdoom backpack product on Shopee. The study employed a qualitative descriptive approach. The data consisted of utterances containing expressive speech acts collected from the product's comment section on Shopee. Data were gathered through a documentation technique in the form of screenshots and analyzed using content analysis. The results revealed five types of expressive speech acts: praising, complaining, criticizing, expressing gratitude, and expressing satisfaction. These speech acts were used by buyers to convey their evaluations, experiences, and responses to the products they received. The findings suggest that product comment sections on e-commerce platforms can serve as relevant data sources for pragmatic studies, as they reflect language use in digital communication.